Re-populating city centres: the role of post-War office to residential conversions - Heath, Timothy Peter (2002)
By the mid-1990s, a new phenomenon of converting obsolete post-war office space into residential use within city centres was beginning to emerge in London, Melbourne, Paris, Toronto and other global cities. This type of development activity has been seen as a panacea for many problems encountered at the end of the twentieth century, including: the ability to meet the increasing demand for new homes; the need to develop in a more sustainable manner; and the desire to revitalise urban and city centres. This thesis concentrates upon such activity in England and identifies that there are five categories of significant barriers and drivers to this process: physical or design-related; locational; financial or economic; demand-related; and legislative factors. The latter two dimensions of the conversion process are examined in detail to reveal the role and impact of the planning system and the perceptions and demand for city centre living particularly in terms of office conversions. The research reveals that the occurrences of post-war office conversions have spread beyond London in the UK, however, its potential remains under exploited due to the impact of the factors identified above. This research therefore plays an important role in furthering the understanding of the demand for and perceptions of city centre residential accommodation together with the advantages and disadvantages of living in these areas. In addition, this thesis identifies the impact of post-war office conversion at a national level and the extent to which the planning system is facilitating or hindering this process. As such, these two potential barriers to conversion activity that have previously been neglected areas of research are analysed in depth and recommendations are made that can facilitate the development process.